Negative interplay between HIV-1 Gag and amyloid precursor protein centers around competition for VPS4A and TSG101 - Feng Gu; Mojgan H. Naghavi (Proceedings of the National Academy of Sciences, 2025)
Intracellular multivesicular bodies (MVBs) act as sites of assembly and release of HIV type 1 (HIV-1) in macrophages and microglia. Recent work has shown that processing of amyloid precursor protein (APP) into a C-terminal fragment (CTF), termed C99, inhibits HIV-1 access to CD63+ MVBs and to counteract this, HIV-1 Group-specific antigen (Gag) increases C99 processing into toxic amyloids. However, the underlying reasons for this negative interplay between Gag and C99 remain unclear. Here, we show that HIV-1 Gag polyprotein and APP processing pathways intersect and compete, relying in different ways on two vesicular trafficking components: the endosomal sorting complexes required for transport protein, TSG101, and vacuolar protein sorting (VPS) subunit, VPS4A. VPS4A plays a complex role in infection by both directly regulating virion production and the abundance of distinct CTFs with differing subcellular localizations and effects on infection. Meanwhile, APP and C99’s use of TSG101 for insertion into vesicles limits Gag access to MVBs. Depletion of TSG101 resulted in impaired Gag localization to MVBs and processing into mature virions, and this could be partially reversed by codepletion of APP. By contrast, modulation of TSG101 or APP levels had no effect on the localization patterns of a Gag-P6 mutant that is unable to bind TSG101, while this mutant also failed to promote C99 degradation. Our findings reveal how CTF processing and HIV-1 maturation at MVBs converge in complex ways around VPS4A and TSG101, which in turn underlies how these processes negatively influence one another during virus replication in microglia.